Effects of UV Exposure on the Physical, Chemical, and Mechanical Properties of Silica Microballoon Reinforced Epoxy Composites - Yunus, Muhammad; Ardhyananta, Hosta; Hidayat, Mas Irfan Purbawanto; Rosidah, Afira Ainur; Laksmono, Joddy Arya; Jayatin, Jayatin; Susanti, Diah; Wijaya, Ade Mundari (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
Epoxy-based composites are widely used in various applications due to their excellent mechanical properties and durability, but their performance under prolonged UV exposure remains a critical concern. This study examines the impact of UV exposure on the physical, chemical, and mechanical properties of epoxy-silica microballoon composites over curing periods of 0, 200, and 400 hours. Results indicate that UV treatment increased the density from 1.0073 g/cm³ to 1.0129 g/cm³. SEM images showed a reduction in fragmentation of epoxy microballoons, indicating stronger bonding. EDX results revealed some changes in elemental composition, with a notable decrease in the percentage of sodium from 0.81 wt.% to 0.18 wt.% and silicon from 7.16 wt.% to 0.12 wt.%. FTIR analysis identified a new hydrogen bond formations at 3350 cm⁻¹. Mechanical testing showed that UV treatment significantly increased the flexural stress from 36.83 MPa to 49.98 MPa. Additionally, hardness (Shore D) increased from 78.4 to 80.2 Shore D. These findings highlighted the significant effects of UV exposure on the structural integrity and bonding mechanisms of the composites, offering valuable insights for their use in UV-prone environments.